Investiční výstavba realizovaná v rámci regionálního rozvoje - Zmrhalová, Adéla (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Cílem diplomové práce je přiblížit problematiku strukturální a regionální politiky EU v České republice a vytvořit všeobecný přehled o fungování čerpání finančních prostředků z fondů EU na konkrétním projektu z pohledu žadatele. Teoretická část se zabývá vznikem Evropské unie a vznikem regionální politiky EU. Dále se zaměřuje na formování regionální politiky v České republice a na projektový cyklus. V praktické části je aplikován projektový cyklus na konkrétní projekt Rozšíření mateřských škol v Jihlavě – Zřízení MŠ Nad plovárnou 5, Jihlava. A to od stanovení cílů, podání žádosti o dotaci a až po realizaci projektu.

The goal of the diploma thesis is to describe the issues of structural and regional policies of European Union in the Czech Republic and to create general knowledge about running of drawing financial resources from EU funds for a particular project from an applicant´s perspective. The theoretical part deals with the origins of European Union and formation of regional policy of EU. Afterwords it is focused on the formation of regional policy in the Czech Republic and the project cycle. In practical part the project cycle is applied on a particular project Enlargement of nursery schools in Jihlava – Nursery school Nad Plovárnou 5, Jihlava from setting the targets, applying for the grant and up to the realization of the project itself.
Investment Construction in the Frame of the Regional Development
Keywords: Evropská unie; Strukturální politika; Česká republika; Strukturální fondy; Regionální rozvoj; Cíl; Dotace; Operační program; Rozpočet; Finance; Projekt; Realizace; Jihlava; Mateřská škola; Implementace; Evropská komise; Vláda; Schválení; Žádost; Žadatel; European Union; Structural Policy; Czech Republic; Structural Funds; Regional Development; Target; Grant; Operational Programme; Budget; Finance; Project; Realization; Jihlava; Nursery School; Implementation; European Comission; Government; Authorization; Application; Applicant